2020
DOI: 10.1080/07434618.2019.1698654
|View full text |Cite
|
Sign up to set email alerts
|

The structure of participants’ turn-transition practices in aided conversations that use speech-output technologies

Abstract: Using the concepts and principles of conversation analysis (CA), this paper examines the everyday unscripted spontaneous conversations between 4 boys who communicate with the aid of a speech-generating device (SGD), and their mothers. The analyses focused on describing the conversationalists' various actions in aided turn-transition processes resulting in a 33-part turntransition structure used to accomplish aided turn initiation. Despite the challenges to conversational progress, the participants did not cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Producing an SGD-mediated contribution is time consuming. In their detailed analysis of SGD-mediated interaction in home settings, Savolainen, Klippi, Tykkyl€ ainen, Higginbotham, and Launonen (2020) found that the process of constructing an SGD contribution took up to 81 s. A few studies have analyzed in detail how the participants handle this lengthy production process. On the one hand, Savolainen et al (2020) found that the communication partners (i.e., mothers) used collaborate practices; they waited in silence or participated in non-competing activities while their children constructed their SGD contributions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Producing an SGD-mediated contribution is time consuming. In their detailed analysis of SGD-mediated interaction in home settings, Savolainen, Klippi, Tykkyl€ ainen, Higginbotham, and Launonen (2020) found that the process of constructing an SGD contribution took up to 81 s. A few studies have analyzed in detail how the participants handle this lengthy production process. On the one hand, Savolainen et al (2020) found that the communication partners (i.e., mothers) used collaborate practices; they waited in silence or participated in non-competing activities while their children constructed their SGD contributions.…”
mentioning
confidence: 99%
“…In their detailed analysis of SGD-mediated interaction in home settings, Savolainen, Klippi, Tykkyl€ ainen, Higginbotham, and Launonen (2020) found that the process of constructing an SGD contribution took up to 81 s. A few studies have analyzed in detail how the participants handle this lengthy production process. On the one hand, Savolainen et al (2020) found that the communication partners (i.e., mothers) used collaborate practices; they waited in silence or participated in non-competing activities while their children constructed their SGD contributions. On the other hand, previous research also demonstrated how the prolonged time producing an SGDmediated contribution could lead to temporal misalignments (i.e., sequential collapse of shared reference and mutual understanding) between the communication partner and the participant relying on the SGD, which resulted in misunderstandings (Clarke & Wilkinson, 2009;Higginbotham & Wilkins, 1999).…”
mentioning
confidence: 99%
“…Their turns also overlapped with spoken turns (Excerpt 3b), or they synchronized their action according to the social context, as Kalle did when he timed his comment with the closing of the door (Excerpt 3c). Some evidence suggests that the turn-transitions of this study appeared to occur in overlapping or latching with the prior turn (48% of turn-transitions) more often than in another study, in which both PS and SBS utterances were used (32 % of the turn-transitions) (see Savolainen et al, 2020). Further research is needed to determine the reasons for this difference.…”
Section: Temporal Resources Of Pre-stored Utterancesmentioning
confidence: 53%
“…By analysing why the PS utterance turns occurred where they did in the sequences, we also recognized that the participants were oriented to furthering the flow of conversations, as other studies of aided and spoken conversations have reported as well (Sacks et al, 1974;Savolainen et al, 2020). During their turn-transitions, the speaking partners allotted time to search for the PS utterance and the aided communicators anticipated their turn by beginning their preparations during their speaking partner's turn, which helped the aided communicators to latch their turn onto a spoken turn (Excerpts 1).…”
Section: Temporal Resources Of Pre-stored Utterancesmentioning
confidence: 92%
See 1 more Smart Citation